TEACHING MODEL OF LEARNING ENGLISH WRITING AT UNIVERSITY - Muhammad Usman (Jurnal Ilmiah Peuradeun, 2015)
The objective of this study is to produce a model of teaching English writing skill in an effective way for students of English Study Program in college. This research method is using the Research and Development. The teaching model arranged can be implemented conceptually and operationally. The model is developed based on the theories of learning writing. This research was conducted in Banda Aceh and the samples for determining the location specified in stratified sampling. This study was conducted at Serambi Mekkah University and Muhammadiyah University. Based on the research findings that the conditions of learning Model at Muhammadiyah University and Serambi Mekkah University were not in accordance with the theory and practice. They need both theory and practice to review paragraphs and the composition should be coherent. The design of learning model, Implementation, and Evaluation could be developed in teaching writing skill for both Universities students.